The PANDA DIRCs - Schwarz, C.; Ali, A.; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; Krebs, M.; Lehmann, D.; Peters, K.; Schepers, G.; Schwiening, J.; Traxler, M.; Schmitt, L.; et al. (Journal of Instrumentation, 2020)
The PANDA experiment at the FAIR facility adresses open questions in hadron physics with antiproton beams in the momentum range of 1.5-15 GeV/c. The antiprotons are stored and cooled in a High Energy Storage RING (HESR) with a momentum spread down to ∆p/p = 4 · 10−5. A high luminosity of up to 2 · 1032 cm−2s−1 can be achieved. An excellent hadronic particle identification (PID) will be provided by two Cherenkov detectors using the priciple of Detection of Internally Reflected Cherenkov light (DIRC). In the forward direction from polar angles of 5◦ to 22◦, the Endcap Disc DIRC (EDD) separates pions from kaons up to momenta of 4 GeV/c. Between 22◦ and 140◦ the Barrel DIRC cleanly separates pions from kaons for momenta up to 3.5 GeV/c. This article describes the design of the Barrel DIRC and of the Endcap Disc DIRC and the validation of their designs in particle beams at the CERN PS.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Cherenkov detectors; Data acquisition concepts; Detector design and construction technologies and materials; Performance of High Energy Physics Detectors